The Effect of the Implementation of the Independent Curriculum and the Work Environment on Work Motivation with Social Competence as a Moderating Variable in Special Needs School Teachers - Asep Setiawan; Kadeni Kadeni; Ajar Dirgantoro (JURNAL PENDIDIKAN IPS, 2025)
The main question addressed in this study is how the implementation of the Independent Curriculum and the work environment influence the work motivation of SLB teachers, and the extent to which social competence strengthens or weakens this relationship. This study aims to analyze the influence of the implementation of the Independent Curriculum and the work environment on teacher work motivation, with social competence as a moderating variable. The method used was quantitative with an explanatory research approach. The study sample consisted of 92 teachers from 12 SLBs in Tulungagung Regency, selected proportionally. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that the implementation of the Independent Curriculum (β = 0.846; p < 0.001) and the work environment (β = 0.846; p < 0.001) had a positive and significant effect on work motivation. However, social competence, as a moderator variable, weakened this relationship (β = -0.563; p < 0.001), indicating that teachers with high levels of social competence tend to face emotional burden and role conflict that hinder motivation. This study suggests the need for psychosocial support and workload management to ensure that social competence does not become a burden, but rather a professional strength for teachers. These findings are expected to serve as a reference for formulating policies to continuously improve the quality of special education teachers.